The Digital Deluge. The essential questions of the humanities in the network society. (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
Our relationship with the social environment is conditioned by information flows in which digital technologies transform any approach and understanding of cultural phenomena. Transcending analog representation systems, digital culture continually generates, modifies, and transmits textual, visual, and sound content. What is the role of the humanities in today's network societies?
Keywords: Digital flood; imaginery material of water; Digital Mercurius